Warning: Increasing Child Marriage in Palu, Sigi, Donggala! - Susilawati, Susi; Maddusila, Sitti Fatimah; Fadjar, Adfiyanti; Nokoe, Nurhayati Sutan; Abdurrahim, Abdurrahim (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2024)
The increase in the number of marriage dispensation cases in the Religious Courts after the amendment of the Marriage Law requires the government to be vigilant. The large number of divorces from young marriages filed with the court is an impact of the increase in the number of marriage dispensation applications. The purpose of this study is to analyze the factors that influence the prevalence of child marriage in Palu, Sigi and Donggala. The method used is socio-legal research method with primary data sources obtained from Penghulu in Palu, Sigi, and Donggala. The results of the study found a strong influence of religious factors, customs, economics, education, pregnancy outside marriage, and narcotics which caused the prevalence of child marriage in Palu, Sigi, and Donggala. All of these influencing factors all lead to the solution of marriage dispensation. A better strategy is needed that is tailored to current conditions. It is also suggested that Penghulu conduct seminars so that they can have the same perception of the Marriage Registration Policy and knowledge of the latest Marriage Law. Cooperation with the courts is needed to facilitate community affairs related to marriage. The police need to increase the eradication of narcotics in areas that are indicated to be places of circulation and abuse. ___ References Books with an author: Kadir, A. (2020). Perspektif Baru Hukum Perkawinan Islam Nikah, Talak, Rujuk. Semarang: Fatawa. Journal articles: Bastomi, H. (2016). Pernikahan Dini dan Dampaknya (Tinjauan Batas Umur Perkawinan menurut Hukum Islam dan Hukum Perkawinan Indonesia). YUDISIA: Jurnal Pemikiran Hukum dan Hukum Islam, 7(2), 354-384. Miqat, N., Patila, M., Kunu, B. D., Mardin, N., & Purwanda, S. (2023). Perkawinan di Desa Kabalutan Kabupaten Tojo Una-Una Perspektif Hukum Perkawinan Indonesia. Media Iuris, 6(2),193-204. Putri, J. E., & Taufik, T. (2017). Kematangan Emosi Pasangan yang Menikah di Usia Muda. JRTI (Jurnal Riset Tindakan Indonesia), 2(2), 1-10. Susilawati, S. (2019, November). Dampak Bencana terhadap Tingkat Perkawinan Anak di Sigi Biromaru. In Unpublished Paper, Delivered at National Symposium (Vol. 30). Susilawati, S., Maddusila, S. F., & Ayyub, M. R. Bersama APRI Memberantas Perkawinan Dini. Jurnal Pengabdian Pada Masyarakat, 9(2), 87-94. Susilawati, S., Ridwan, A., & Madusila, S. F. (2021). Criminal Liability against Perpetrators of Fraudulent Criminal Act by Hynosis. Tadulako Law Review 6(1), 40-49. Purwanda, S., Bakhtiar, H. S., Miqat, N., Nur, R., & Patila, M. (2022). Formal Procedure Versus Victim's Interest: Antinomy of Handling Sexual Violence Cases In East Luwu. Jurnal Hukum Volkgeist, 6(2), 116-122. Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163.